Determination of procalcitonin in serum and ascites of patients with dialysis-related peritonitis - WANG Fu-xu; LIANG Gui-rong; CHEN Guang; LU Guan-jie; HOU Jia-xing; WU Fang; SU Xiao-fang (Linchuang shenzangbing zazhi)
Objective To investigate the levels of procalcitonin(PCT) in serum as well as pritoneal diadysate in patients with peritoneal dialysis-related peritonitis. Methods 124 patients undergoing peritoneal dialysis and 62 healthy subjects were enrolled in this study from June 2014 to February 2017. In patients given peritoneal dialysis, there were 63 patients with peritoneal dialysis-related peritonitis and 61 patients with non-peritoneitis. The levels of PCT in serum and ascites were determined by electrochemiluminescence immunoassay. The white blood cell(WBC) counts and PCT levels in ascites were detected in patients receiving peritoneal dialysis. Results Before treatment, the levels of serum PCT were significantly higher in peritonitis group than those in non-peritonitis group or healthy group(P<0.01). In pritoneal diadysate, the levels of PCT and the WBC counts were significantly increased in peritonitis group than those in non-peritonitis group(P<0.01). There were no significant differences in serum PCT among the three groups after treatment(P>0.05). In pritoneal diadysate, the levels of PCT and the WBC counts showed no significant difference between peritonitis group and non-peritonitis group after treatment(P>0.05). Conclusions The PCT levels in serum and ascites are significantly increased in patients with peritoneal dialysis-related peritonitis. The PCT can be used as a predictive factor in patients with peritoneal dialysis-related peritonitis.